Network Dependence in the Euro Area Money Market - Gerhard Rünstler (European Central Bank (ECB), 2016)
I estimate network dependence effects in the euro area unsecured overnight interbank market during the financial crisis. I use linear spatial regressions to estimate the dependence of individual banks?trading volumes (and interest rates) on the trading volumes (and interest rates) of their network neighbours. Neighbours are defined from past trading relations. I find that banks?net lending volumes and lending-borrowing interest rate spread depend negatively on their neighbours? respective outcomes. By contrast, there arise positive effects for total trading volume and borrowing rates. Overall, however, these effects are small and significant only in periods of market turmoil or of major policy interventions. The results suggest that neighbours act as a buffer in absorbing idiosyncratic liquidity shocks.
Keywords: C21; E42; 330; euro area money markets; financial crisis; network analysis; spatial regressions